Spontaneous physical functional recovery after hospitalization for COVID-19: insights from a 1 month follow-up and a model to predict poor trajectory - Honchar, Oleksii; Ashcheulova, Tetyana (Frontiers in Medicine, 2023)
Background. Long COVID syndrome has emerged as a new global healthcare challenge, with impaired physical performance being a prominent debilitating factor. Cardiopulmonary rehabilitation is a mainstay of management of symptomatic post-COVID patients, and optimization of candidate selection might allow for more effective use of available resources. Methods. In order to study the natural dynamics and to identify predictors of physical functional recovery following hospitalization for COVID-19, 6-minute walk test was performed pre-discharge in 176 patients (40% hypertensive, 53% female, mean age 53,2±13,5 years) with re-evaluation at 1 month. Results. 6-minute walk distance and the reached percent of predicted distance (6MWD%) were suboptimal at both visits -396±71 m (68,7±12,4%) pre-discharge and 466±65 m (81,8±13,6%) at 1 month. Associated changes included significant oxygen desaturation (2,9±2,5 and 2,3±2,2%, respectively) and insufficient increment of heart rate during the test (24,9±17,5 and 28,2±12,0 bpm) that resulted in low reached percent of individual maximum heart rate (61,1±8,1 and 64,3±8,2%). Automatic clusterization of the study cohort by the 6MWD% changes has allowed to identify the subgroup of patients with poor "low base -low increment" trajectory of spontaneous post-discharge recovery that were characterized by younger age (38,2±11,0 vs 54,9±12,1, p<0,001) but more extensive pulmonary involvement by CT (43,7±8,8 vs 29,6±19,4%, p=0,029) and higher peak ESR values (36,5±9,7 vs 25,6±12,8, p<0,001). Predictors of poor recovery in multivariate logistic regression analysis included age, peak ESR, eGFR, percentage of pulmonary involvement by CT, need for in-hospital oxygen supplementation, SpO2 and mMRC dyspnea score pre-discharge, and history of hypertension. Conclusions. COVID-19 survivors were characterized by decreased physical performance predischarge as assessed by the 6-minute walk test and did not completely restore their functional status after 1 month of spontaneous recovery, with signs of altered blood oxygenation and dysautonomia contributing to the observed changes. Patients with poor "low base -low increment" trajectory of post-discharge recovery were characterized by younger age but more extensive pulmonary involvement and higher peak ESR values. Poor post-discharge recovery in the study cohort was predictable by the means of machine learning-based classification model that used age, history of hypertension, need for oxygen supplementation, and ESR as inputs.